The outcome of late versus early ileostomy closure at low body weight (<1500 g) in babies with necrotizing enterocolitis - Pradyumna Pan (Wolters Kluwer Medknow Publications, 2022)
Aim: The aim of this study is to determine the surgical outcome of ileostomy closure at low body weight (<1500 g) and to find any differences in complications and growth of infants whose ileostomy was reversed early (4-6 weeks) versus late (8-10 weeks). Methods: A prospective comparative study was conducted on patients who underwent ileostomy reversal created for necrotizing enterocolitis from January 2017 to December 2019. The patients were divided into two groups: group 1 (early ileostomy closure) between 4 and 6 weeks and Group 2 (late closure) between 8 and 10 weeks. The primary outcome was expressed as the presence of anastomotic leak, obstruction, perforation, wound infection, sepsis, and death. Results: A cohort of 31 patients with 16 patients in Group 1 and 15 in Group 2 were studied. The mean duration between ostomy creation and reversal was 5.1 ± 0.63 weeks in Group 1 and 8.9 ± 0.66 weeks in Group 2. The mean weight at reversal was 1435.5 ± 163.8 g for patients in Group 1 and 1405 ± 99.93 g for patients in Group 2. Weight gain at 90 days in Group 1 was 895 ± 85.2 g and in Group 2 was 455 ± 34.6 g, which was statistically significant (P < 0.00001). Parenteral nutrition, ability to reach full enteral nutrition, and total ventilator days, mortality rate, and complications were not statistically different between the groups. The overall survival rate was 87.27%. Conclusions: Ileostomy reversal at a lower weight and within 6 weeks was not associated with an increased risk of complications. Early stoma reversal may help in weight gain.